Utilization of Galectins by Pathogens for Infection - Ayona, Diyoly; Fournier, Pierre-Edouard; Henrissat, Bernard; Desnues, Benoit (Frontiers in Immunology, 2020)
Galectins are glycan-binding proteins which are expressed by many different cell types and secreted extracellularly. These molecules are well-known regulators of immune responses and involved in a broad range of cellular and pathophysiological functions. During infections, host galectins can either avoid or facilitate infections by interacting with host cells- and/or pathogen-derived glycoconjugates and less commonly, with proteins. Some pathogens also express self-produced galectins to interfere with host immune responses. This review summarizes pathogens which take advantage of host- or pathogen-produced galectins to establish the infection.